A load-velocity relationship for men and women in overhead throwing performance - Marques, M. C.; Marinho, D. A.; van den Tillaar, R. (Journal of Sports Science & Medicine, 2010)
TIn many movements, resistance (load) and velocity are inversely related to each other (Schilling et al., 2008). This relationship is often ascribed to skeletal muscle properties. Hill, 1938 described a hyperbolic relationship (Hill's curve) between force and velocity for isolated muscles. Many other researchers in muscle physiology as well as researchers in the more applied sciences used this association to describe and explain phenomena of muscle contraction. In sport science, many training studies, set up to enhance the performance of the athlete, are based on Hill's curve (e.g. Schilling et al., 2008; van Den Tillaar and Ettema, 2004).